Pengaruh Kualitas Layanan dan Komitmen Petugas Terhadap Kepercayaan Pasien dan Kepuasan Pasien Rawat Jalan di UPTD Puskesmas Tamiang Layang Kabupaten Barito Timur - Hedi Gunawan D. Sinto (KINDAI, 2023)
Health Centers are required to provide quality health services supported by the commitment of officers so as to provide patient trust and satisfaction. This study aims to determine the effect of service quality and staff commitment on the trust and satisfaction of outpatients at the UPTD Tamiang Layang Health Center. This research is a quantitative study with a population of all outpatients at the Tamiang Layang Health Center UPTD with a sample of 288 people, using a purposive sampling method. Data analysis using Partial Least Square based Structural Equation Model. The results showed that there was an effect of service quality on patient trust, there was an effect of staff commitment on patient trust, there was an effect of service quality on patient satisfaction, there was an effect of staff commitment on patient satisfaction, and there was an effect of patient trust on patient trust. Keywords: Service Quality, Commitment, Trust, Satisfaction